The role of experiences and sociability networks in the construction of narratives in enterprises - Lozano, Rafael Baldomero López (Technium Social Sciences Journal, 2019)
This article seeks to know the role of experiences and networks of sociability in the nation's narratives among a group of businessmen and executives belonging to various business associations in Lima. These perceptions, representations and experiences were developed within the framework of the thesis "Analysis of the discourse on Peruvian society in the main business associations of Lima". Thus, research stems from the need to study the most privileged sectors of Peruvian society from anthropology because it helps to understand how power is exercised in Latin America.